Cotton, Biotechnology, and Economic Development - Baffes, John (2012)
During the past decade, cotton prices remained considerably below other agricultural prices (although they recovered toward the end of 2010). Yet, between 2000-04 and 2005-09 world cotton production increased 13 percent. This paper conjectures that biotechnology-induced productivity improvements increased supplies by China and India, which, in addition to keeping cotton prices low, aided these countries to cap-ture market share from (and cause losses to) non-users of biotechnology. By contrast, with a single exception, Africa has not adopted biotechnology and, not coincidentally, its cotton output declined by more than 20 percent between the first and second half of the past decade. The paper concludes that the development implications of biotechnology go beyond cotton and Africa. High energy prices have been an important driver of the recent commodity price boom. Therefore, investment and policy strategy responses to a cost-driven boom should be consistent with cost-saving alternatives. Biotechnology clearly meets this challenge.